2018
DOI: 10.1111/labr.12127
|View full text |Cite
|
Sign up to set email alerts
|

How Differences in Cash Transfer Sizes Affect Work Allocation Decisions: Evidence from Cross‐Country Comparisons in SSA

Abstract: Over the past decade, several African governments have launched Cash Transfer (CT) programmes as part of their social protection systems, with the aim of reducing poverty. Such programmes can also have significant productive impacts. We use data from four major CT programmes implemented in sub-Saharan Africa to estimate their impacts on labour supply and demand and how effects change in relation to transfer size. We find evidence of labour reallocation between farm and off-farm work and limited evidence of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…FAO contributed with an analysis of the impacts on productive activities and labour supply (Daidone et al, 2014), a local economy study on the income multipliers generated by the CGP (Taylor et al, 2014) and a qualitative analysis of the CGP on household income and community dynamics (OPM, 2014). Overall, these and other companion studies found many areas where the CGP brought about positive impacts, such as: i) increased levels of household expenditure on schooling and health needs for children, largely due to the programme's "messaging" (OPM, 2014;Pace et al, 2018); ii) some increase in food security, especially for indicators on children, and dietary diversity (Pellerano et al, 2014;Tiwari et al, 2017); iii) small decrease in casual labour, but no overall "dependency effect" (Daidone et al, 2014;Prifti et al, 2018); iv) increased farm production and relevant income…”
Section: Introductionmentioning
confidence: 99%
“…FAO contributed with an analysis of the impacts on productive activities and labour supply (Daidone et al, 2014), a local economy study on the income multipliers generated by the CGP (Taylor et al, 2014) and a qualitative analysis of the CGP on household income and community dynamics (OPM, 2014). Overall, these and other companion studies found many areas where the CGP brought about positive impacts, such as: i) increased levels of household expenditure on schooling and health needs for children, largely due to the programme's "messaging" (OPM, 2014;Pace et al, 2018); ii) some increase in food security, especially for indicators on children, and dietary diversity (Pellerano et al, 2014;Tiwari et al, 2017); iii) small decrease in casual labour, but no overall "dependency effect" (Daidone et al, 2014;Prifti et al, 2018); iv) increased farm production and relevant income…”
Section: Introductionmentioning
confidence: 99%
“…The Zambia Child Grant Program (CGP) provided a fixed bi‐monthly transfer of 60 Kwacha per month ($US17), to ultra‐poor households with children under five, 98.3 per cent of which were female‐headed households (Daidone et al ., 2015; Prifti et al, 2018). Evaluation based on a randomized controlled trial showed that the CGP facilitated the purchase of agricultural inputs and assets leading to an increase in production (Daidone et al, 2015).…”
Section: Introductionmentioning
confidence: 99%